2009
DOI: 10.1509/jmkr.46.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Off Aversion as an Explanation for the Attraction Effect: A Functional Magnetic Resonance Imaging Study

Abstract: This research reports on a cognitive neuroscientific examination of whether trade-off aversion explains the attraction effect. The principal study involves the neuroimaging of participants engaging in choice tasks while their cerebral activity is recorded. The authors examine whether the presence of a third (normatively irrelevant) alternative yields relatively less activation in areas of the brain associated with negative emotion than the activation during choice tasks involving two equally (un)attractive opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 40 publications
9
100
1
2
Order By: Relevance
“…Analyzing brain activity another influence of the choice set itself can be shown, which is that trade-off choice sets trigger relatively higher negative emotions. Thus, the influence of irrelevant alternatives on choices between multi-attribute products can be explained (Hedgcock and Rao 2008). Furthermore, in a recent paper it was shown that the ranking between a prospect and a sure payoff within a choice set can depend on the choice set itself (Bateman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing brain activity another influence of the choice set itself can be shown, which is that trade-off choice sets trigger relatively higher negative emotions. Thus, the influence of irrelevant alternatives on choices between multi-attribute products can be explained (Hedgcock and Rao 2008). Furthermore, in a recent paper it was shown that the ranking between a prospect and a sure payoff within a choice set can depend on the choice set itself (Bateman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to this explanation, agents employ a decision strategy in which they first look for a dominance relation between alternatives and choose the dominating alternative if such a relation exists. This hypothesis is also supported by the findings of a Magnetic Resonance Image (MRI) study that show people avoid trade-off contrast and search for dominance (Hedgcock and Rao, 2009). Another experimental investigation of the asymmetric dominance effect where two-outcome lotteries are used as choice alternatives is Herne (1999).…”
Section: Introductionmentioning
confidence: 74%
“…In line with H 1A , we also found increased activation in the right cingulate gyrus (BA 24). For the decision sets that included the FCB e , the FCB e was selected in, on average, 97.48 (SD=3.29) out of 100 possible 46), the right medial frontal gyrus (BA 8), and the right middle frontal and left precentral gyrus (both BA 6)-with all areas part of the DLPFC (Hedgcock and Rao 2009;Schott et al 2011). Mean reaction times for TD blocks (M=960 ms; SD= 205 ms) were lower than those for DD blocks (M=1457 ms; SD=251 ms), t(24)= 13.81, p<.001.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve these goals, we selected functional magnetic resonance imaging (fMRI) as our research approach (for an overview of the method see, e.g., Ariely and Berns 2010;Shiv et al 2005) because there is reason to believe that fMRI will help marketing research by understanding how emotions are processed in the brain (Lieberman 2007;Strack and Deutsch 2004). This reasoning is primarily based on the notion that neuroscientific methods such as fMRI (a) are considered to be more objective than self-report data (Dimoka 2010;Yoon et al 2009); (b) are able to capture unconscious, emotional processes Yoon et al 2012); and (c) investigate participants' responses during decision-making (Craig et al 2012;Hedgcock and Rao 2009). The latter may be particularly important, as the responses during decision-making may differ from post hoc rationalizations after a decision is made (Reimann et al 2010;Smith 2002).…”
Section: Introductionmentioning
confidence: 99%